Survey Tingkat Percaya Diri Pelajar Putri dalam Ekstrakurikuler Pencak Silat di SMK Se-Kabupaten Karawang (Study di SMKN 1 Karawang) - Eka Apriyani; Aria Kusuma Yuda; Ardawi Sumarno (Peneliti.net, 2021)
This study aims to determine the level of self- confidence of students in participating in extracurricular pencak silat activities at State Vocational Schools throughout Karawang Regency (study at SMK Negeri 1 Karawang) based on the belief in self-ability, optimism responsibility, objective and rational factors. The subjects in this study were female students who took extracurricular pencak silat. The data collection technique used in this study was a questionnaire. The method used is a survey, while the data collection technique uses a questionnaire, the questionnaire in this study is in the form of a Likert scale. The results of the study revealed that the level of self- confidence of the pencak silat extracurricular participants in Karawang Regency was stated in the very low category with a percentage of 5%, in the low category with a percentage of 30%, in the medium category with a percentage of 35%, in the high category with a percentage of 18%, in the very high category with a percentage of 13%.